TITUS FLAVIUS IOSEPHUS'UN HAYATI, ESERLERİ VE TARİHÇİLİĞİ. - DEMİR, Muzaffer; ÖZER, Ebru (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2020)
Titus Flavius Josephus, a Jewish monk, had served as one of the Galilee commanders during the Jewish uprising against Rome (66-70 AD) until his arrest as a result of siege laid by Rome on Jotapata (Yodfat). After this shortterm military career, he was awarded by the Roman commander Vespasian to spend the rest of his life, far way from his homeland, at Rome as a historian, thanks to his prophecy that Vespasian would be emperor in future. By having taken the ancient Greek historians, particularly both Polybius and Thucydides as his model, he had composed four masterpieces: Wars of the Jews in which he focuses on the armed conflicts between Jews and Rome; Antiquities of the Jews where he tells the accounts of the Jews since the beginning of the world until his own time; his autobiography called as Vita and finally Against Apion in which he defends himself and Judaism. In this study, by taking into account especially the first hand accounts including his own and the modern sources, we will make explanations regarding the life and the works as well as the historiography of Josephus.